Effect of pentobarbital anesthesia on amikacin concentrations in plasma and perilymph and evaluation of multiple sampling in perilymph of guinea pigs. - Desjardins-Giasson, S (1985)
The purpose of this study was to determine whether a multiple-sampling procedure could be used in guinea pigs to study the kinetics of amikacin in perilymph. Amikacin was infused intravenously for 6 h into conscious anesthetized guinea pigs, and the concentrations of the drug in plasma and perilymph were measured. From each anesthetized guinea pig, five to six perilymph samples were collected from one ear, and one sample was collected from the other ear at 6 h. The concentrations of amikacin in perilymph were dose proportional and increased slowly during the 6-h infusion. However, after 6 h of intravenous infusion, the concentrations of amikacin in perilymph of the multiply sampled ears were significantly higher than those of the singly sampled ears, indicating that the multiple-sampling procedure should not be used as is to study the kinetics of amikacin in perilymph. Amikacin concentrations in perilymph were linearly related to amikacin concentrations in plasma in pentobarbital-anesthetized animals, as had previously been observed for conscious guinea pigs. However, the slope of the regression line was only 0.09 for anesthetized animals compared with 0.24 for conscious animals. Drug concentrations in plasma were found to be threefold higher in anesthetized animals, whereas drug levels in perilymph were the same in both groups at similar dosing rates. These results indicate that the amikacin concentration in perilymph is not solely dependent upon its concentration in plasma and that other factor(s) can affect the entry of amikacin into the inner ear.